Differences in lower body kinematics during forward treadmill skating between two different hockey skate designs - Hellyer, M. R.; Alexander, M. J. L.; Glazebrook, C. M.; Leiter, J. (International Journal of Kinesiology & Sports Science, 2016)
Purpose: The purpose of this study was to investigate the differences in ankle flexibility and skating technique between a traditional hockey skate boot and a hockey skate boot with a flexible rear tendon guard. Skating technique was further investigated at different speeds to give insight on how skating technique alters as skating speed is increased. Methods: Eight elite hockey players were selected for the present study, which was conducted while skating on an Endless Ice Skating Treadmill. Variables were recorded using a three-camera setup and measured from video records at five selected treadmill speeds using the Dartfish Team Pro v6 software. Kinematic variables were then compared between the two skate designs with a doubly multivariate repeated measures design. Statistical significance was set at p<0.05. Results: Post hoc univariate tests comparing skate designs displayed significant increases in plantar flexion, plantar flexion angular velocity, hip extension, hip extension angular velocity, stride length, and stride velocity while participants were wearing the skates that had a flexible rear tendon guard. Significant increases were also displayed in plantar flexion, plantar flexion angular velocity, knee extension, knee extension angular velocity, hip extension, hip extension angular velocity, hip abduction range of motion, hip abduction angular velocity, stride width, stride length, and stride velocity as the treadmill speed increased. There was also a significant decrease in the time the skate was in contact with the treadmill as treadmill speed increased. Conclusion: The results suggested that while skating forward, hockey players could improve their hockey skating technique by using hockey skates that have a flexible rear tendon guard. This flexible tendon guard improved skating technique by increasing the time of force application to the ice by increasing the range of ankle plantar flexion during propulsion of the forward skating stride.